2019
DOI: 10.1016/j.dci.2019.103449
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-22 protein and IL-22-producing cells in rainbow trout Oncorhynchus mykiss

Abstract: IL-22 is a critical cytokine which is involved in modulating tissue responses during inflammation, and is produced mainly by T cells and innate leucocytes. In mammals, IL-22 is a key component in mucosal defences, tissue repair, epithelial cell survival and proliferation. In teleosts, IL-22 has been cloned and studied in several species, and the transcript is highly expressed in mucosal tissues and induced by pathogen associated molecular patterns (PAMPs), suggesting IL-22 also functions as an important compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
2
8
2
Order By: Relevance
“…Interestingly, the suppression is observed during early infection, suggesting that this could be a virus-regulated effect. This inhibitory effect contrasts previous findings in rainbow trout gills after infection with A. salmonicidae, where IL-22 was strongly upregulated (47). In that study, the infection was shown to increase the number of IL-22 producing cells in the gill epithelium and interbranchial lymphoid tissue (47).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Interestingly, the suppression is observed during early infection, suggesting that this could be a virus-regulated effect. This inhibitory effect contrasts previous findings in rainbow trout gills after infection with A. salmonicidae, where IL-22 was strongly upregulated (47). In that study, the infection was shown to increase the number of IL-22 producing cells in the gill epithelium and interbranchial lymphoid tissue (47).…”
Section: Discussioncontrasting
confidence: 96%
“…This inhibitory effect contrasts previous findings in rainbow trout gills after infection with A. salmonicidae, where IL-22 was strongly upregulated (47). In that study, the infection was shown to increase the number of IL-22 producing cells in the gill epithelium and interbranchial lymphoid tissue (47). IL-22 is expressed by innate T-cells (γδ T cells), abundant in mucosal tissue (48).…”
Section: Discussioncontrasting
confidence: 94%
“…IL-22 was constitutively expressed in most tissues with immune-related functions in healthy grass carp but was more highly expressed in the gills and hindgut (Figure 2). This observation is consistent with previous studies in which basal transcription was higher in mucosal tissues such as in the gills, pyloric cecae, and the intestine (12,14,17,20,23). These studies have suggested that IL-22 may mediate inflammation and facilitate the maintenance of homeostasis of the mucosal barrier in order to provide protection against pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…Further, it was found that IL-22 was markedly upregulated at mucosal sites in fish infected with gram-negative or gram-positive bacterial pathogens (15). Recently, IL-22-producing cells were characterized in rainbow trout (Oncorhynchus mykiss) and were found to reside in gill filaments and interbranchial lymphoid tissues, having accumulated thereafter the fish infected with Aeromonas salmonicida (20). That study demonstrated that IL-22 is a key regulator, which coordinates the immune responses against bacterial pathogens (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation